On the symbol of nonlocal operators associated with a parabolic diffeomorphism - Izvarina, Natalia (Eurasian Mathematical Journal, 2018)
We study the ellipticity of the symbols of operators associated with parabolic diffeomorphisms of spheres and we show, that if for some smoothness exponent of the Sobolev space the symbol of an operator is invertible, then the symbol is invertible for all exponents of Sobolev spaces.